A privacy-preserving handover authentication protocol for a group of MTC devices in 5G networks. Issue 116 (May 2022) - Yan, Xiaobei; Ma, Maode
Abstract: Machine Type Communication (MTC) has been emerging for a wide range of applications and services for the Internet of Things (IoT). In some scenarios, a large group of MTC devices (MTCDs) may enter the communication coverage of a new target base station simultaneously. However, the current handover mechanism specified by the Third Generation Partnership Project (3GPP) Release 16 incurs high signaling overhead over the access network and the core network for such scenario. Moreover, other existing solutions have several security problems in terms of the failure of key forward secrecy (KFS) and lack of mutual authentication. In this paper, we propose an efficient authentication protocol for a group of MTCDs in all handover scenarios. By the proposal, the messages from two MTCDs are concatenated with an aggregated message authentication code (MAC) and sent by an authenticated group member to reduce the signaling cost. The proposed protocol has been formally evaluated by Scyther tool to prove its security. And it has been analysed on its security functionality to show its ability to resist major typical malicious attacks. Temporary identities of MTCDs have been used to preserve users' privacy. It can be expected that the proposed protocol is applicable to all kinds of group mobility scenarios such as a platoon of vehicles or a high-speed train. The performance evaluation demonstrates that the proposed protocol is efficient in terms of computational, communication, signaling, and energy cost.